A case of congenital single testis with testicular cancer patient and azoospermia who was able to collect spermatozoa with ipsilateral Onco‐TESE. Issue 1 (23rd November 2020) - Hayashi, Kazumasa; Inamoto, Teruo; Azuma, Haruhito; Masuda, Hiroshi; Oku, Hirotsugu
Abstract: Onco‐TESE is a useful strategy for cancer patients with a congenital single testis who wish to preserve their fertility. Abstract : Onco‐TESE is a useful strategy for cancer patients with a congenital single testis who wish to preserve their fertility.